Liver-Directed Surgery for Metastatic Squamous Cell Carcinoma to the Liver - Pawlik, Timothy (2007)
Background The role of hepatic resection for metastatic squamous cell carcinoma (SCC) remains unknown. The current study evaluates the role of hepatic resection in patients with metastatic SCC to the liver. Methods Between 1988 and 2006, 52 patients underwent hepatic resection of metastatic SCC at eight major cancer centers. Clinicopathologic factors were analyzed with regard to disease-free survival (DFS) and overall survival (OS). Results Primary SCC site was anal (n = 27), head/neck (n = 12), lung (n = 4), esophagus (n = 2), and other (n = 7). Treatment of primary SCC was chemotherapy ± radiotherapy alone (n = 29), chemotherapy ± radiotherapy + surgery (n = 15), or surgery alone (n = 8). Forty-seven patients underwent resection alone, 2 resection + radiofrequency ablation (RFA), and 3 RFA only. At last follow-up, 33 (63.5%) patients had recurred. The median time to recurrence was 9.8 months, and 5-year DFS was 18.6%. Factors associated with reduced DFS were liver tumor size > 5 cm (hazard ratio (HR) = 2.02) and positive surgical margin (HR = 2.33). The overall median survival after hepatic resection was 22.3 months and 5-year actuarial OS was 20.5%. Risk factors associated with worse overall survival included synchronous disease (HR = 4.09), hepatic metastasis > 5 cm (HR = 1.71) and positive surgical resection margin (HR = 1.83). Conclusions The majority of patients will recur following hepatic resection of SCC. Long-term survival, however, can be achieved following surgical resection of SCC liver metastasis, especially in patients who present with limited metachronous disease amenable to margin negative resection.